Ibm Bagi Petani Benih Udang Windu Skala Rumah Tangga (Backyard) Di Desa Kalitengah Kecamatan Tanggulangin Sidoarjo Yang Mengalami Gagal Panen Berkepanjangan Karena Serangan Penyakit [Ibm For Seed Shrimp Farmers Family Scale (Backyard) In Kalitengah Village, Tanggulangin District, Sidoarjo Region, That Harvesting Lossed To Long Times That Caused By The Diseases] - Gunanti Mahasri; Sudarno Sudarno; Endang Dewi Masithah (Faculty of Fisheries and Marine Universitas Airlangga, 2014)
Abstract Demand of seed shrimp, as specially tiger shrimps is still not enough until now, it is only 5060%, more than for 5-10 years end showed decreased point. One of factors that influenced the successfully seeds shrimp hatchery is water quality that as a life media of shrimps. A bisnis about shrimp hatchery is still have a good market, because there are a lot of tiger shrimp pond operational, more than some time demand of the shrimp increase fluctuative on seasonal. The aims of this this societies service activities is applicated a new shrimp hatcher technology by using immunostimulant at Putri Mandiri Group company, it aplicated in family hatcher in Kalitengah village, Tanggulangin District, Region of Sidoarjo. The immunostimulant use to increase the body deffence of the shrimp larve in hatchery to the disease attacked dan invirontment during culture periode, it will be increase the harvesting. The method using in the activity were socialitation/counseling, dempond and guiding to application of the method of shrimp hatcher by using immunostimulant in one periode. Monitoring and evaluation about this result were done in one month after the activity ending. This result showed that aplicated immunostimulant in shrimp family hatcher Backyard) can increased the shrimp seed harvesting of Putri Mandiri Company owner, from 900.000 to 1.600.000 shrimp seeds, it is same as that the profit increased from 8.622.000,- until 15.822.000,- Rupiahs for one periode panen for one container 10 tonage capacity.